Study on adsorption of lead and cadmium by non-burning ceramic granules from waterworks residual sludge. Issue 1 (November 2020) - Tang, Haiyun; Zhao, Yuanyuan; Li, Yaoyu; Liu, Danni; Chen, Yuehui; Xu, Youze
Abstract: In this experiment, the unburned ceramiste water treatment residuals (UCWTR) was prepared by the burning-free method to study its adsorption performance on Pb and Cd. Adsorption experiments show that the quality of ceramsite improved with the height of the filler layer in the reaction column, and its penetration and depletion time are prolonged. On the contrary, the driving force of mass transfer increases with the initial concentration of water in the reaction column, and the penetration and exhaustion time is shortened. The dynamic adsorption process of Pb and Cd by UCWTR is more consistent with the Thomas model and Yoon-Nelson model, and the correlation coefficient R2 is greater than 0.9. Under the condition that the initial flow rate v is 10 mL/min, the height of the packing layer h is 10 cm, and the initial concentration C0 is 150 mg/g, the fitted dynamic saturated adsorption capacities of UCWTR for lead and cadmium are 9.22 mg/g, 11.52 mg/g, the static adsorption capacity of lead and cadmium are 1.48 times and 155 times respectively. kT decreases as the height of the filler layer and the initial concentration increase; kYN decreases as the height of the filler layer increases, and increases as the initial concentration increases; the time t required to penetrate 50% of the adsorbent increases with the height of the filler layer and decreases with the increase of the initial concentration, which indicated that the solution did not reach full contact with UCWTR during the dynamic adsorption process.